Effects of Higher Equity Ratio on a Bank's Total Funding Costs and Lending - Bent Vale (Norges Bank, 2011)
Simply stating that because equity is much more expensive than debt funding, banks total funding costs will increase accordingly if their equity ratio is increased, biases the estimated increase upwards. As recently put forwards in the literature, one has to take into account that higher equity ratio lowers the volatility of equity and hence its required return. In addition, higher equity ratio makes a bank's debt safer and lowers the required return on debt. Taking these two effects into account the Modigliani-Miller theorem implies that a bank's total cost of funding should not be influenced by the bank's equity ratio. However, the existence of explicit or implicit guarantees may reduce the latter effect and cause a bank's total funding cost to increase somewhat when the equity ratio is raised. Miles, Yang, and Marcheggiano (2011) studying UK banks find a slight increase in their funding costs if the equity ratio is increased. Applying the estimates of Miles et.al. we find that a hypothetical doubling of DnB NOR Bank's equity ratio from 5.5 to 11 per cent would increase its total funding costs in the range of 11 to 41 basis points. In steady state such an increase in Norwegian banks' funding costs could reduce lending by 0.33 to 1.23 per cent. In the short run, an abrupt increase in banks' required capital could however cause significantly larger reductions in lending due to frictions in the market for issuing equity
hdl:11250/2507326
Keywords: 330